PERAN NILAI ISLAM MEMBENTENGI REMAJA DARI PERGAUALAN BEBAS - Nurmadiah Nurmadiah; Lismayana Sahabuddin; Herawati Syamsul (JPMUJ, 2026)
Adolescence is a phase of identity search full of dynamics. Teenagers begin to want recognition, try new things, and are often influenced by their environment and social media. Amid the rapid currents of globalization and technological advancement, moral values are often neglected, resulting in deviant behavior such as free association. Free association is a deviant behavior that violates the social, religious, and legal norms prevailing in society. This term is often associated with negative actions beyond reasonable limits, especially among adolescents. This behavior includes promiscuity, drug use, excessive alcohol consumption, and other criminal acts. The implementation of Community Service activities with the theme 'The Role of Islamic Values in Shielding Teenagers from Free Association' is based on the basic concept that Islamic values are one of the components of the rules or religious norms that apply in community life It is very important for every person as a guideline in their social life, especially for teenagers in every aspect of their interactions, so that they can avoid every type of free association. This Community Service activity is carried out in the form of counseling and education with the theme of The Role of Islamic Values in Shielding Teenagers from Free Association in Lonjoboko Village, Parangloe District, Gowa Regency, South Sulawesi Province. The results achieved from the implementation of this community service activity are: increased knowledge of teenagers about the Role of Islamic Values as a Moral Shield, instilling a sense of shame and responsibility, directing the energy and potential of teenagers, fostering social control and an Islamic environment, strategies for forming Islamic teenagers, as well as the exemplary role of parents and teachers.